EFFECT OF LATISSIMUS DORSI STRENGTHENING IN THORACOLUMBAR DYSFUNCTION - AHMAR K. ANSARI; G. VARADHARAJULU (International Journal of Psychosocial Rehabilitation, 2020)
An experimental study was conducted to find out the effect of latissimus dorsi strengthening exercises in reducing pain, improving activities of daily living in thoracolumbar dysfunction. The study was conducted on 30 subjects both male and female sexes. The subjects were selected on the basis of convenience and availability with follow-up during the study process. A detailed history, thorough assessment and examination was carried out. All the subjects were assessed with the outcome measures (for pain by Visual Analogue Scale (VAS), functional status by Modified Oswestry Low Back Pain Disability Questionnaire and amplitude of Latissimus Dorsi Muscle by EMG Analysis) prior to enrollment for the exercise therapy as baseline values. Subjects in Group A received latissimus dorsi strenghthening exercises, whereas, subjects in Group B received conventional exercises. The exercises to all the subjects were given for a week. Later, they continued the exercises at home. Then follow up was done at 1 month. After successful completion of the training phase i.e on follow up, subjects were reassessed on all of the outcome measures. The study shows that there was a significant improvement in reducing pain, improving activities of daily living (ADLs) and Motor recruitment in Latissimus Dorsi Muscle in subjects with thoracolumbar dysfunction. CONCLUSION-Based on the results and interpretation it was found that the latissimus dorsi strengthening exercises along with the conventional exercises was effective in reducing pain, improving activities of daily living (ADLs) and Motor recruitment in Latissimus Dorsi Muscle in subjects with thoracolumbar dysfunction.